2003
DOI: 10.1046/j.1524-4725.2003.29292.x
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Minute Application of the S-Caine Peel Prior to Nonablative Laser Treatment

Abstract: The S-Caine Peel provided effective and safe dermal anesthesia after only a 30-minute application period for nonablative laser treatment with the 1450-nm diode laser. The unique vehicle readily delivers anesthetic to contoured regions of the body and eliminates the need for occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
(28 reference statements)
1
16
0
Order By: Relevance
“…Another common topical lidocaine formulation, LMX, uses liposomes as the delivery method for improved penetration and for sustained release of the anesthetic agent (4 % lidocaine) even after the cream is removed from the skin [6, 11]. Both of these topical treatment options are effective at relieving pain, but they require lengthy application times and occlusion, and may provide inadequate anesthesia at peripheral skin margins [11, 12]. EMLA cream has proven to have anesthetic efficacy in several clinical trials involving such dermatologic procedures as cryotherapy, pulsed dye laser treatment, and debridement of leg ulcers [1316].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another common topical lidocaine formulation, LMX, uses liposomes as the delivery method for improved penetration and for sustained release of the anesthetic agent (4 % lidocaine) even after the cream is removed from the skin [6, 11]. Both of these topical treatment options are effective at relieving pain, but they require lengthy application times and occlusion, and may provide inadequate anesthesia at peripheral skin margins [11, 12]. EMLA cream has proven to have anesthetic efficacy in several clinical trials involving such dermatologic procedures as cryotherapy, pulsed dye laser treatment, and debridement of leg ulcers [1316].…”
Section: Methodsmentioning
confidence: 99%
“…Lidocaine/tetracaine cream has the highest approved concentrations of lidocaine and tetracaine that has also proven to be safe and effective in producing local dermal anesthesia for dermatological procedures [12]. Its novel vehicle functions as a self-occluding cream—the product is applied as a cream that dries to a pliable membrane upon exposure to air [6, 12]. This unique formulation allows for easy application, removal, and access to areas deemed difficult for other topical anesthetics.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical studies have demonstrated the effectiveness of a peel forming cream containing lidocaine/tetracaine mixture to provide satisfactory anaesthesia and reduce the time of onset of action compared to a cream and or placebo during dermatologic surgery [104,105]. A positive patient experience has been reported with the use of peels, studies have confirmed that the peel is well tolerated with side effects limited to localized and transient skin reactions, which do not interfere with clinical outcome [104][105][106]. The self occluding nature of the peel may play a vital role in promoting drug absorption and enhancing the duration of action of topically applied medicaments.…”
Section: Topical Peels /Film Forming Productsmentioning
confidence: 99%